Mucin-1 Protein Is a Prognostic Marker for Pancreatic Ductal Adenocarcinoma: Results From the CONKO-001 Study - Striefler, Jana Käthe; Riess, Hanno; Lohneis, Philipp; Bischoff, Sven; Kurreck, Annika; Modest, Dominik Paul; Bahra, Marcus; Oettle, Helmut; Sinn, Marianne; Bläker, Henrik; Denkert, Carsten; Stintzing, Sebastian; et al. (Frontiers in Oncology, 2021)
Background: The Mucin-family protein, MUC1 impacts on carcinogenesis and tumour invasion. We evaluated the impact of MUC1 expression on outcome in a cohort of 158 patients with resected pancreatic ductal adenocarcinomas (PDAC) in the CONKO-001 study (adjuvant gemcitabine [gem] vs. observation [obs]). Methods: The percentage of MUC1-positive tumour cells by immunohistochemistry (IHC) and the staining intensity were evaluated by 2 observers blinded to outcome. The numeric values of both parameters were multiplied, resulting in an immunoreactivity score (IRS) ranging from 0 to 12. Low versus high MUC1 expression was defined based on data distribution (IRS 0-4 vs IRS >4). Outcomes in terms of disease-free (DFS) and overall survival (OS) were evaluated by Kaplan-Meier method, log-rank tests and Cox regressions. Results: In total, tumours of 158 study patients were eligible for immunohistochemistry of MUC1. High cytoplasmic MUC1 expression was associated with impaired DFS and OS in the overall study population (hazard ratio (HR) for DFS: 0.49, 95% CI 0.31 to 0.78, p=.003; HR for OS: 0.46, 95% CI 0.29 to 0.73, p=.001). In the study arms, prognostic effects of MUC1 were also evident in the observation group (HR for DFS: 0.55; 95% CI 0.29 to 1.04, p=.062; HR for OS: 0.34, 95% CI 0.17 to 0.67, p=.001) and trending in the gem group (HR for DFS: 0.48, 95% CI 0.24 to 0.95, p=.041; HR for OS: 0.56, 95% CI 0.28 to1.11, p=.093). Conclusion: Our data suggest that MUC1 expression is a powerful prognostic marker in patients with PDAC after curatively intended resection.